The Fate of Aldicarb Residue in Groundwater at a Central Sand Plain Farm, Waushara County, Wisconsin - Bruce, John W. (University of Wisconsin-Stevens Point, College of Natural Resources, 1985)
Groundwater is depended upon by a large proportion of the people of Wisconsin, as well as America, for drinking and many other domestic, agricultural, and industrial purposes. In spite of this dependence, groundwater statewide and nationwide is being extensively contaminated with low levels of toxic chemicals which may impact to some degree on human and animal health. Therefore, groundwater should be studied so we may better understand the fate of potentially harmful chemicals. Aldicarb is an insecticide which has been widely used on potatoes in the Central Sand Plain of Wisconsin and which has leached into groundwater in many parts of that region and the U.S. In Wisconsin, an administrative rule, pesticide label restrictions, and legislation were made to limit aldicarb leaching but some doubt their effectiveness. Groundwater at a Central Wisconsin farm was monitored for residues of aldicarb and for certain inorganic chemicals. 42 multi-level and standard PVC groundwater sampling devices were constructed and installed at 26 sites for this and other related studies. Groundwater samples were collected at 1-3 month intervals from November 1981 to April 1984. An additional study was conducted to determine if aldicarb degrades under laboratory conditions. Aldicarb occurred in the groundwater in a distinct plume characterized by a high aldicarb concentration layer in its mid-section and decreasing aldicarb concentrations above and below that layer. Observations indicated the plume was traveling at a rate of 1.4 ft/day, and that it had traveled a total of 1956 ft by the end of the study. The depth of the maximum aldicarb concentration layer increased 5-10 ft below both the ground level and the water table over the study period. The maximum depth of the plume was 18.3 ft in October 1983. The plume thickness was 6 ft in May 1982, 12 ft in October 1982 and between 2 and 8 ft in February 1984. The highest aldicarb concentration in February 1982 was 114 ppb whereas it was 8 ppb in February 1984. The half-life for aldicarb in the groundwater was calculated to be 206 days. In a laboratory study aldicarb half-lives in three samples were calculated to be 1916, 1520, and 478 days. Half-lives were inversely related to pH and alkalinity concentrations. Concentration zones of certain inorganic chemicals tracked with the maximum aldicarb concentration layer over time. This indicated that these chemicals move similar to aldicarb in groundwater.